APLICAÇÃO DO ESTATUTO DA CIDADE EM SALVADOR NO SÉCULO XXI: O DISCURSO E A PRÁTICA - Santana, Celia Regina Sganzerla (2011)
This text offers a critical view on the implementation of Law 10.257/01, The City Statute (EC), in Salvador, a decade after its adoption. The study is based on research on the formation of cities and on Brazilian urban planning genesis. The work focuses on the city of Salvador (Bahia) urban planning process, particularly after 1980s, when Masters Plans began to incorporate the EC´s principles, and mainly, after the 2000s, when EC´s ideas become more explicit in the Masters Plans (PDDU). Based on the history of this process and on specialists expectations, professionals from various sectors involved in the urban planning process, a discussion is developed about the limits and possibilities of EC´s implementation in Salvador, at the end of the first decade of the XXI Century. The result shows that the EC's proposals to Salvador, which privilege public interest and space, remained on paper and the use of some urban instruments is deviating from its original principles, helping to worsen problems of public resources waste, corruption and excessive density in the city.